Selecting Total Quality Management (TQM) Best Practices in the Hotel Industry Environment : A Hybrid Model based on DEMATEL and ANP - Sin, Kit Yeng; Lo, May Chiun; Abang Azlan, Mohamad; Abdullah, Al Mamun; Choon, Ling Sim (Kharazmi University, 2023)
Recently, developing strategies for sustainable development (SD) in the hotel industry has been seen globally as a crucial issue. Numerous management systems can assist the hotel industry in creating sustainable performance, such as Total Quality Management (TQM) which is well-reputed in the industry. As such, selecting TQM under an evolving hotel industry environment is seen as an important decision from a strategic perspective given it constitutes contradictory practices, thereby making it a multi-criteria decision-making (MCDM) issue. In achieving this aim, a Decision-Making Trial and Evaluation Laboratory (DEMATEL) approach was adopted in determining the inter-relationships between the primary practices and sub-practices in addition to applying the Analytic Network Process (ANP) for examining the weights of primary practices and sub-practices. In other words, this study aims to provide innovative insight to researchers and practitioners to examine the TQM optimal practices to be implemented incrementally in phases within the hotel industry environment.